Exploration of Wedelia trilobata, Acmella paniculata, Ageratum conyzoides, and Crassocephalum crepidiodes as Antibacterial Plants - Ryadi, Yusuf; Alzamori, Winda; Batubara, Irmanida; Suparto, Irma Herawati (Jurnal Jamu Indonesia, 2023)
Some Asteraceae plants are reported to contain phytochemicals and to show high antibacterial activity. This study aims to determine the highest antibacterial activity of Wedelia trilobata, Acmella paniculata, Ageratum conyzoides, and Crassocephalum crepidiodes and to predict the chemical compounds that have a role as antibacterial. The samples were extracted with water and further fractionated using chloroform in the laboratory. Extracts determined the phytochemical compounds, antibacterial activity diffusion method, and compounds that have a role as antibacterial through literature review. Acmella paniculata demonstrated high antibacterial activities with the highest diameter of the zones of inhibition with a concentration of just 0.5 mg/disc. The compound that seems to have a role in antibacterial activity is spilanthol.